2023
DOI: 10.1177/14680874231153302
|View full text |Cite
|
Sign up to set email alerts
|

A parametric study to improve first firing cycle emissions of a gasoline direct injection engine during cold start

Abstract: A parametric study was carried out for the first firing cycle of a 4-cylinder, 2.0-liter, turbocharged gasoline direct injection (GDI) engine. The primary goal was to see how changes in the fuel injection parameters would affect the GDI engine combustion and emissions for the first four combustion events that constitute the first firing cycle. Experimental studies were carried out with a custom-designed powertrain control system to measure the HC emissions and pressure development for the first firing cycle. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…HC emissions are a primary concern for engine cold start, especially for the first several cycles, as mentioned in the introduction section. The simulation results of the fuel tracking using the FES model for the very first firing cycle are presented as the Sankey graphs in another paper 51 of ours, along with experimental measurements. That study showed that there are thick fuel films (26% of total injected fuel) on the cylinder and piston walls at a very late crank angle of the very first firing cycle.…”
Section: Discussionmentioning
confidence: 99%
“…HC emissions are a primary concern for engine cold start, especially for the first several cycles, as mentioned in the introduction section. The simulation results of the fuel tracking using the FES model for the very first firing cycle are presented as the Sankey graphs in another paper 51 of ours, along with experimental measurements. That study showed that there are thick fuel films (26% of total injected fuel) on the cylinder and piston walls at a very late crank angle of the very first firing cycle.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of the engine speeds using the 2-inj and 4-inj strategies is provided as Figure 3 in our previous paper. 14 In particular, for the intake strokes of cylinders 2 & 1, seen in that figure, the engine speed with the 4-inj strategy significantly surpassed that of the 2-inj strategy, enhancing the engine intake turbulence intensity, making a direct comparison of the effects of the normalized turbulence more complicated. Nevertheless, the overall effect is presented in Figure 4 of that same paper 14 : the combustion process for all four cylinders was greatly enhanced in the improved strategy, with the least increase of peak pressure for cylinder 1 (the last one to fire), where the engine speed increased the most.…”
Section: Improved Strategymentioning
confidence: 92%
“…The high-resolution transient engine speed was captured and calculated based on the pulse signals of a rotational incremental encoder, which was installed on the flywheel. Figure 3 depicts a schematic diagram of the experimental setup, and more information can be found in previous papers 12,14 from our team.…”
Section: Experiments Setupmentioning
confidence: 99%